2015
DOI: 10.1007/s11515-015-1359-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of upstream stimulatory factor 2 in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is the most common cause of end-stage renal disease (ESRD). About 20%–30% of people with type 1 and type 2 diabetes develop DN. DN is characterized by both glomerulosclerosis with thickening of the glomerular basement membrane and mesangial matrix expansion, and tubulointerstitial fibrosis. Hyperglycemia and the activation of the intra-renal renin-angiotensin system (RAS) in diabetes have been suggested to play a critical role in the pathogenesis of DN. However, the mechanisms are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Moreover, Ang II can stimulate the expression and activation of oxidative stress protein p66Shc in tubular epithelial cells (TECs) and participate in the oxidative damage of tubular cells through induces the overproduction of ROS in tubular cells mitochondria. In addition, high glucose can up-regulate Ang II expression in various renal cells, which can induce the accumulation of ECM and promoting the renal fibrosis of DN (Wang 2015). Generally, the mechanism of Ang II-induced renal fibrosis includes the promotion of hypertrophy and proliferation of MCs through the TGF-β signaling pathway (Meng et al 2012).…”
Section: Angiotensin IImentioning
confidence: 99%
“…Moreover, Ang II can stimulate the expression and activation of oxidative stress protein p66Shc in tubular epithelial cells (TECs) and participate in the oxidative damage of tubular cells through induces the overproduction of ROS in tubular cells mitochondria. In addition, high glucose can up-regulate Ang II expression in various renal cells, which can induce the accumulation of ECM and promoting the renal fibrosis of DN (Wang 2015). Generally, the mechanism of Ang II-induced renal fibrosis includes the promotion of hypertrophy and proliferation of MCs through the TGF-β signaling pathway (Meng et al 2012).…”
Section: Angiotensin IImentioning
confidence: 99%
“…The dysregulation of FOXC1 is involved in skeletal abnormalities [30]. The USF2 is also involved in diabetic nephropathy [31]. Dysregulation of YY1 in the liver causes insulin resistance, dyslipidemia etc and has also been proposed as targeting hepatic YY1 an important target for insulin-resistant diabetes [32].…”
Section: Discussionmentioning
confidence: 99%
“…As for Gdh, starvation decreased hepatic mRNA levels of Usf2 in the liver of S. aurata. In this regard, it was previously reported that high glucose levels upregulate Usf2 expression in human-derived HK-2 cells and primary rat mesangial cells (Shi et al 2008, Visavadiya et al 2011, Wang 2015. Therefore, low levels of glycemya associated to long-term starvation may be critical to downregulate Usf2 expression, which in turn may lead to decreased Gdh mRNA levels in the liver of S. aurata.…”
Section: Figurementioning
confidence: 94%